The Role of English in Employment Context: the Case of Indonesian Chinese Company - Aam Alamsyah; Santosa Santosa; Radik Darmawan; Mutaat Mutaat; Fitria Ningsih (IKIP PGRI Pontianak, 2024)
The role of English in Indonesian pedagogical field has been studied extensively. However, the role of English in the employment context is scarcely scrutinized. Given the increasing awareness of being employable, examining the functions of international languages demanded in the employment context is imperative. The study focuses on some crucial aspects of English in the employment context, such as the workers' motivation toward English, the goals in learning English, and the potential hardships or challenges in learning or practicing English in their employment context. In order to capture more varied data, the researchers employed a mixed method along with a G-form questionnaire, interviews, and document analysis. The recruited participants comprised of sixty active employees who are currently working as permanent employees in a Chinese company. The participants were recruited randomly. The result indicated that even though English was the employees' preferred foreign language, they preferred to learn it through informal sources (e.g., YouTube, Google Translate, and Grammarly). It was also found that only few departments used English in the company (e.g., marketing, sales department, export- import department). The primary language used to support the company's production was Chinese/Mandarin. The outcome should encourage further research on the factories or businesses owned by non-English nationals (e.g., Japanese, or Korean) so that the critical role of English in the current employment contexts can be verified.